Randomized phase II study of fulvestrant plus palbociclib or placebo in endocrine-sensitive, hormone receptor-positive/HER2–advanced breast cancer: GEICAM/2014–12 (FLIPPER). (January 2022) - Albanell, J.; Martínez, M.T.; Ramos, M.; O'Connor, M.; de la Cruz-Merino, L.; Santaballa, A.; Martínez-Jañez, N.; Moreno, F.; Fernández, I.; Alarcón, J.; Virizuela, J.A.; de la Haba-Rodríguez, J.; et al.
Abstract: Background: The potential benefit of adding palbociclib to fulvestrant as first-line treatment in hormone receptor (HR)-positive, human epidermal growth factor receptor 2 (HER2)-negative endocrine-sensitive advanced breast cancer (ABC) patients remains uncharacterized. Patients and methods: In this randomized (1:1), double-blind, phase II study, postmenopausal women with HR-positive, HER2-negative ABC with de novo metastatic disease or those who relapsed after >12 months of adjuvant endocrine therapy received palbociclib/fulvestrant or placebo/fulvestrant. Stratification was based on recurrent versus de novo metastatic disease and visceral involvement. The primary objective was one-year progression-free survival (PFS-1y) rate. The sample size was 190 patients. The two-sided alpha of 0.2, 80% of power to detect a difference between the arms, assuming PFS rates of 0.695 and 0.545 for palbociclib/fulvestrant and placebo/fulvestrant, respectively. Results: In total, 189 patients were randomized to palbociclib/fulvestrant ([ n  = 94] or placebo/fulvestrant [ n  = 95]). 45.5% and 60.3% of patients had de novo metastatic disease and visceral involvement, respectively. PFS-1y rates were 83.5% and 71.9% in the palbociclib/fulvestrant and placebo/fulvestrant arms, (HR 0.55, 80% CI 0.36–0.83, P  = 0.064). The median PFS were 31.8 and 22.0 months for the palbociclib/fulvestrant and placebo/fulvestrant arms (aHR 0.48, 80% CI 0.37–0.64, P  = 0.001). The most frequent grade 3–4 adverse events were neutropenia (68.1% vs. 0%), leucopenia (26.6% vs. 0%), anemia (3.2% vs. 0%), and lymphopenia (14.9% vs. 2.1%) for the palbociclib/fulvestrant and placebo/fulvestrant, respectively. The most frequent non-hematologic grade 3–4 adverse event was fatigue (4.3% vs. 0%). Conclusions: Palbociclib/fulvestrant demonstrated better PFS-1y rates and median PFS than placebo/fulvestrant in HR-positive/HER2-negative endocrine-sensitive ABC patients. Highlights: Palbociclib + fulvestrant as first-line improved the 1-year PFS rate in ABC patients. Palbociclib + fulvestrant significantly improved median PFS. Palbociclib + fulvestrant had a manageable safety profile.